COMPORATIVE STUDIES ON DESTRUCTIVE BENDING MOMENTS OF T-SHARPE CORNER JOINTS OF FRAME STRUCTURAL ELEMENTS MADE OF SWEET CHESTNUT WOOD WITH A CROSS SECTION OF 50 X 25 MM (Innovation in Woodworking Industry and Engineering design, 2026)
The results from the research on the tightness characteristics of the middle angle combi-nations details from massive chestnut wood with a cross section of 50 x 25 mm used in the construction of seating furniture have been given.It has been found, that according to the point of the damaging bending moment, the unassembling middle angle combinations are arranged in the following falling order: through conductive oval knot and tenon type A ; through an unconductive oval knot and tenon type A ; through conductive oval knot and tenon type B ; through oval knot and tenon type B ; through two dowels 10 mm ; through oval plated knot and tenon.According to the point of the damaging bending moment, the assembling middle angle combinations are arranged in the following falling order: through two one elements joints type „Confirmat“; through two screws for timber; through two joints with screw and cross dowel, Swedish type.The results from the research are recommended to be used in the measurement of the furniture for sitting.